The Relationship Between Corporate Culture, Social Responsibility and Increasing the Competitiveness of the Enterprise - LISHCHYNSKYI, M. P. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
Abstract. The article examines the applied conditionality and investigates the theoretical foundations of forming Corporate Social Responsibility (CSR) and Corporate Culture (CC). The primary purpose of this research is to uncover the essence and reveal the content of the concepts "Corporate Social Responsibility" and "Corporate Culture," as well as to generalize the specific features of the influence of a corporate culture built on the principles of social responsibility on company competitiveness. In pursuit of this objective, Corporate Social Responsibility is examined in both the narrow and broad senses. A general description of business social responsibility concepts is provided. It is emphasized that within the framework of CSR, it is conventional to distinguish between internal and external responsibility, and that this internal responsibility is precisely the Corporate Culture. A relationship is established between reputation, company image, Corporate Social Responsibility, and Corporate Culture. The main definitions are systematized, and the key features of the concepts "Corporate Culture" and "Corporate Social Responsibility" are highlighted. The results of building a corporate culture on the principles of social responsibility that supports the company’s development strategy are outlined.